Navigating Surrogacy - Kulshrestha, Sandeep (Revista Amagis Jurídica, 2023)
Surrogacy is taboo in the society, though it is important and gives an objective to the lives of a large number of couples. Present Paper is based on an empirical study conducted by the researcher among the surrogates in and around south Indian City Hyderabad. He deals with the analysis of the concept of surrogacy from the moral, social and feminist views along with the views of Surrogates and people of their vicinity. Psychological impact has also been analysed. It is also found that the surrogates are in high spirit of being instrument of exultant for others and represent it an altruistic work. Though it is not socially accepted, but people of the vicinity of the surrogates don’t consider as taboo.